Single-dose tafenoquine to prevent relapse of Plasmodium vivax malaria - Lacerda, MVG; Llanos-Cuentas, A; Krudsood, S; Lon, C; Saunders, DL; Mohammed, R; Yilma, D; Batista Pereira, D; Espino, FEJ; Mia, RZ; Chuquiyauri, R; Val, F; et al. (Massachusetts Medical Society, 2019)
Background Treatment of Plasmodium vivax malaria requires the clearing of asexual parasites, but relapse can be prevented only if dormant hypnozoites are cleared from the liver (a treatment termed “radical cure”). Tafenoquine is a single-dose 8-aminoquinoline that has recently been registered for the radical cure of P. vivax.